Pembrolizumab in a Patient with Treatment-Naïve Unresectable BRAF-Mutation Negative Anaplastic Thyroid Cancer - Fadi Nabhan; Elizabeth Kander; Rulong Shen; Amit Agrawal; Vineeth Sukrithan; Ye Zhou; Ashima Goyal; Katie Roll; Manisha Shah; Bhavana Konda (Case Reports in Endocrinology)
Immune check point inhibitor (ICI) therapy can be a potentially effective salvage treatment for anaplastic thyroid cancer (ATC) with progression despite standard of care therapies. We report a case of unresectable treatment-naïve ATC showing a dramatic and durable response to first-line pembrolizumab therapy. A 69-year-old male presented with a large, right-sided neck mass associated with compressive symptoms. A neck ultrasound showed a large, right-sided, and highly suspicious thyroid nodule. A fine needle aspiration (FNA) biopsy revealed tumor cells consistent with ATC that were positive for PD-L1, with an expression score of >95% and negative for the BRAF V600E mutation. Imaging studies were negative for distant metastases. The disease was declared surgically inoperable, and the patient declined chemotherapy/radiation therapy (XRT), but agreed to ICI therapy with intravenous pembrolizumab 200 mg every three weeks. The patient has received 25 doses of pembrolizumab to date, with rapid resolution of symptoms and a significant reduction in tumor size. He remains alive without disease progression 18 months since initial diagnosis.